Benchmarking Methodology For International Oil Companies Based On The Hybrid Strategy And Strategic Performance - Al Sayed Noor, Alhamzah Malik Radhi (2022)
Porter's new strategy (from now on referred to as the hybrid strategy) is based on a mix of differentiation and cost leadership. The literature on hybrid strategy confirms the investigation of such a strategy is mostly limited. With the suspicion of the pure strategies (i.e., differentiation, cost leadership, and focus) are active in strategic performance. Several open issues and challenges facing the implementation of a hybrid strategy and not been observed yet. This study aims to explore the influence of the context factors for the hybrid strategy on the strategic performance through the mediating variable, the content factors for the hybrid strategy. In addition, the researcher explores the strength of the relationship between the content factors for the hybrid strategy and the strategic performance through the interaction of readiness for change. To this end, this study completes the previous literature with a combination of the partial least squares structural equation modeling (PLS-SEM) and multicriteria decision-making (MCDM). Thus, the MCDM (i.e., best-worst-method [BWM] and vlsekriterijumska optimizcija i kaompromisno resenje [VIKOR]) are effective approachs to solving the problem of complexity and evaluation (i.e., multiple evaluation criteria, important criteria, and data variation).